2022
DOI: 10.3389/fped.2022.749323
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Distress During Early Life Periods and Offspring Respiratory Infections and Allergic Outcomes

Abstract: BackgroundIncreasing evidence suggests that maternal distress is a risk factor for development of respiratory infections and allergic diseases in the offspring. We aim to evaluate the link between maternal distress during critical periods in early life, namely the preconception, pregnancy and postnatal periods, and development of respiratory infections and allergic diseases in the offspring from the Singapore PREconception Study of long Term maternal and child Outcomes (S-PRESTO) cohort.MethodsMaternal perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Schoolchildren in China were found to have a higher likelihood of developing rhinitis if their mothers had symptoms of depression during and after pregnancy ( 70 ). A cohort study from Singapore showed that elevated scores of maternal depression before conception and during pregnancy were associated with a greater chance of the offspring developing wheezing within the initial 18 months of life ( 71 ). A meta-analysis also showed a positive association between maternal depression or anxiety and asthma in offspring ( 72 ).…”
Section: Common Risk Factors For Allergy and Tdmentioning
confidence: 99%
“…Schoolchildren in China were found to have a higher likelihood of developing rhinitis if their mothers had symptoms of depression during and after pregnancy ( 70 ). A cohort study from Singapore showed that elevated scores of maternal depression before conception and during pregnancy were associated with a greater chance of the offspring developing wheezing within the initial 18 months of life ( 71 ). A meta-analysis also showed a positive association between maternal depression or anxiety and asthma in offspring ( 72 ).…”
Section: Common Risk Factors For Allergy and Tdmentioning
confidence: 99%